Draft Fourth Five Year Plan 1969-74 Government of Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1968)
Goa, Daman and Diu were constituted as a separate Union Territory in 1962, after their liberation from Portuguese rule on December, 19, 1961. The Territory comprises three land blocks on the West Coast separated from each other by a distance of over 300 miles. Administratively also, the Territory is divided into three districts, respectively named Goa, Daman and Diu. The boundaries of Goa district are defined, in the north by the Terekhol river which separates it from Maharashtra, in the east and south by Mysore State and in the west by the Arabian Sea. The district of Daman is bounded, on the north by he Bhagwan river, on the east by Gujarat State, on the south by the Kalem river and on the west by the Arabian Sea.
Government of The Union Territory of Goa ,Daman and Diu Planning Department